PENGARUH KERAGAMAN PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN OPPO SMARTPHONE PADA MAHASISWA UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Edy Kusnadi Hamdun; Nurhasana Nurhasana (Growth, 2018)
This research uses descriptive method involving 97 respondents. Date collection was done by literature study, interview, and questionnaire distribution. The data obtained were analyzed by using the statistic formula, that is by using multiple regression analysis, T test, F test, and coefficient of determination which was done by SPSS version 22 windows 13. This research is divided into four independent variables, product diversity (X1) , Price (X2) and promotion (X3) and one dependent variable is purchase decision (Y). The result of descriptive analysis shows that product diversity variables (X1), price (X2), and promotion (X3) have a positive influence on purchase decision variable (Y), it is shown in result of multiple linear regression analysis Y = 4,975E-17 + 0,186 + 0.320 + 0.278 + e. The result of t test shows the value for product diversity variable is 2.037> 1,985, the value for the Price variable is 3,111> 1,985 and the value for promotion variable is 2,586> 1,985. The result of simultaneous statistical test or F test shows the value of 23,024> 2,70. The result of dominant statistical test of dominant price variable is 3,111.